IMMUNOMODULATORY EFFECTS OF GARLIC AND TULSI IN REPEAT BREEDING CROSSBRED COWS
Role of crude extracts of garlic and tulsi as an agent to stimulate uterine defense mechanism was studied by examining total protein and immunoglobulins in uterine flushing of repeat breeding cows and compared with most sensitive antibiotic (enrofloxacin), selected on the basis of antibiogram. Forty crossbred repeat breeding cows with endometritis were selected on the basis of history, appearance of cervical mucus and white side test after thorough per-rectal examination. Cows were divided randomly into five groups viz.A, B, C, D and E (control). 30 ml crude extracts of garlic, tulsi, garlic+tulsi, diluted with distilled water (1 :5) were infused intrauterine, thrice, at 24 hrs interval starting on day of estrum in cows of group A, B and C, respectively. Similarly, enrofloxacin, selected on the basis of antibiO!Jram (30 ml